Prevalence and Associated Factors of Self-Medication among Pregnant Women on Antenatal Care Follow-Up at University of Gondar Comprehensive Specialized Hospital in Gondar, Northwest Ethiopia: A Cross-Sectional Study - Sema, Faisel Dula; Addis, Deres Gezahegn; Melese, Eshetie Azezew; Nassa, Demeke Dana; Kifle, Zemene Demelash (International Journal of Reproductive Medicine, 2020)
Background. Self-medication is being prevalent throughout the globe. Although pregnant women are among the most vulnerable group of the population for drug-induced adverse effects on their fetus and themselves, many pregnant women use self-medication without adequate safety precautions. Objective. This study was aimed at assessing the prevalence and associated factors of self-medication among pregnant women on antenatal care follow-up at University of Gondar Comprehensive Specialized Hospital. Methods. A cross-sectional study was employed among 400 pregnant women attending antenatal care clinic at the University of Gondar Comprehensive Specialized Hospital between February 01 and May 30, 2019. A structured interviewer-administered questionnaire was used for data collection. Data were analyzed using SPSS® (IBM Corporation) version 22. Descriptive statistics were presented using frequency and proportion. Binary logistic regression was used to identify factors associated with self-medication with a 95% confidence level and p value of 0.05. Results. Among 400 respondents, the prevalence of self-medication during the current pregnancy was 44.8% (95% CI=40.5-50). Among all respondents (400), 38.0% (95% CI=33.3-42.8) and 12.5% (95% CI=9.5-15) used herbal and conventional medicine, respectively. Self-medication showed a significant association with a previous history of self-medication and monthly income. Conclusions. The prevalence of self-medication among pregnant women is considerably high. The previous history of self-medication and monthly income showed a significant association with self-medication. Awareness creation should be done for reproductive-age women on the potential risks of self-medication.